The weather man - Cage, Nicolas, 1965-; Verbinski, Gore.; Caine, Michael; Davis, Hope, 1967-; Rispoli, Michael; Bellows, Gil.; Papamichael, Phedon; Zimmer, Hans.; Paramount Pictures Corporation ([Hollywood, Calif.] : Paramount Pictures, 2006)
Dave Spritz is a local weatherman in his home town of Chicago. His career is going well, but his personal life is spiraling downward. His relationship with his perfectionist writer father, his neurotic ex-wife, and his now-separated children have him feeling that his life is out of control. Despite being both loathed and loved by the local masses, Dave is a guy who just doesn't seem to have it all together. An attractive job offer from New York City presents Dave with a major question - to pursue his career or to remain at home with his family.
Originally released as a motion picture in 2005.
Special features: Extended outlook: the script; forecast: becoming a weatherman; atmospheric pressure: the style and palette; relative humidity: the characters; trade winds: the collaboration; theatrical trailer.
Director of photography, Phedon Papamichael ; editor, Craig Wood ; music, Hans Zimmer ; costume designer, Penny Rose ; production designer, Tom Duffield
Nicolas Cage, Michael Caine, Hope Davis, Michael Rispoli, Gil Bellows.
MPAA rating: R; for strong language and sexual content.
DVD; region 1; NTSC; full screen (1.33:1) presentation.
Keywords: Television weathercasters -- Illinois -- Chicago -- Drama; Weather forecasting -- Illinois -- Chicago -- Drama; Interpersonal relations -- Illinois -- Chicago -- Drama; Feature films; Comedy films; Video recordings for the hearing impaired